Activation of ACS7 in Arabidopsis affects vascular development and demonstrates a link between ethylene synthesis and cambial activity. (14th September 2020) - Yang, Shuo; Wang, Sining; Li, Shujia; Du, Qian; Qi, Liying; Wang, Wenguang; Chen, Jingtang; Wang, Huanzhong
Abstract: Ethylene is a gaseous hormone that affects many processes of plant growth and development. During vascular development, ethylene positively regulates cambial cell division in parallel with tracheary element differentiation inhibitory factor (TDIF) peptide signaling. In this study, we identified an ethylene overproducing mutant, acs7-d, exhibiting enhanced cambial activity and reduced wall development in fiber cells. Using genetic analysis, we found that ethylene signaling is necessary for the phenotypes of enhanced cambial cell division as well as defects in stem elongation and fiber cell wall development. Further, the cambial cell proliferation phenotype of acs7-d depends on WOX4, indicating that the two parallel pathways, ethylene and TDIF signaling, converge at WOX4 in regulating cambium activity. Gene expression analysis showed that ethylene impedes fiber cell wall biosynthesis through a conserved hierarchical transcriptional regulation. These results advance our understanding of the molecular mechanisms of ethylene in regulating vascular meristem activity. Abstract : The ethylene overproducing mutant acs7-d reveals a new molecular mechanism of how ethylene regulates the vascular meristem, enhancing our understanding of ethylene function in secondary growth.